The innovation process in the energy industries - Ray, G. F.; Uhlmann, Luitpold; The National Institute of Economic and Social Research (Cambridge England ; New York : Cambridge University Press, 1979)
The inquiry into the process of industrial innovation in German, British, and Swedish companies was conducted by a group of European economic research institutes. The object is to study the process of research and development, and the implementation of new technologies, by investigating examples of innovation in the energy sector, including its suppliers and consumers.
Includes index.
ne 24/04/2018
Loans
Keywords: Energy industries